Cryptography on a Speck of Dust. - Kaps, Jens-Peter; Gaubatz, Gunnar; Sunar, Berk (Computer (00189162), 2007)
The article discusses the security problems with wireless sensor networks (WSNs) and radio frequency identification (RFID) devices whose applications range from supply-chain management to home automation and health care. Since these devices are extremely small and have limited power, the task of applying security requires cryptographic services that can perform on a minuscule sized area. The authors give an overview of current cryptographic algorithms and then apply those ideas on a extremely small level. The article continues by giving design recommendations for new algorithms. INSET: Ultralow-Power Application Domain.